Local Wisdom Tafsir Nusantara: An Analysis of Language Style in Tafsir al-Ibriz - Ghofur, Abdul; Fatkhiyati, Naily (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
The books of tafsir in regional languages in Indonesia are the result of the local mufassir's shrewdness in harmonizing the language of the Qur'an and adaptation to the surrounding social and cultural background. The existence of this, is able to produce works of interpretation that make it easier for the interpreting community to read it as well as the vernacularization of the Qur'an. One of them is the book of Tafsir al-Ibriz. This research discusses the style of language and vernacularization in Tafsir al-Ibriz by KH. Bisri Musthofa Rembang. By using the literature method, this research produces descriptive analysis data, among others: the existence of interactive language styles of interpretation such as jajal pikiren, analogies of interpretation such as umpamane mengkene, vernacularization of terms such as Ora tau rewel, ora tau ndongkrok, and Javanese proverbs such as becik ketitik ala ketara in Tafsir al-Ibriz.  This means that there is local wisdom in the treasures of the archipelago's interpretation. Kitab-kitab tafsir  berbahasa daerah di Indonesia merupakan buah hasil dari kelihaian mufassir lokal dalam menyelaraskan antara bahasa al-Qur’an dan adaptasi dengan latar belakang sosial dan budaya di sekitarnya. Adanya hal tersebut, mampu menghasilkan karya tafsir yang memudahkan masyarakat tafsir dalam membacanya seperti halnya vernakularisasi al-Qur’an. Salah satu  di anataranya yaitu kitab Tafsir al-Ibriz. Penelitian ini membahas tentang gaya bahasa dan vernakularisasi dalam Tafsir al-Ibriz karya KH. Bisri Musthofa Rembang. Dengan menggunakan metode kepustakaan, penelitian ini menghasilkan data analisis deskriptif  antara lain: adanya gaya bahasa interaktif penafsiran seperti jajal pikiren, analogi penafsiran seperti umpamane mengkene, vernakularisasi istilah  seperti Ora tau rewel, ora tau ndongkrok, dan peribahasa jawa seperti becik ketitik ala ketara dalam Tafsir al-Ibriz.  Ini berarti terdapat local wisdom dalam khazanah tafsir  nusantara.